2016
DOI: 10.3390/agriculture6030031
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Exogenous Application of Salicylic Acid on Physiological Characteristics, Proline and Essential Oil Content of Chamomile (Matricaria chamomilla L.) under Normal and Heat Stress Conditions

Abstract: Abstract:The objective of this study was to investigate the effect of exogenous application of salicylic acid concentrations on the physiological and biochemical traits and essential oil content of chamomile under normal and heat stress conditions as induced by delayed sowing. The experiments were conducted during 2011-2012 as a factorial using a randomized complete block design with three replications, in a very hot region. The factors included five salicylic acid concentrations (0 (control), 1, 10, 25 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Capsicum P n values varied more in our experiment (3.6-3.7 to 16.3 mmol CO 2 /m 2 /s fixed) than they did in other experiments reported by others; for example, Ou and Zou (2012) reported that the P n of five Capsicum species varied from 15.8 to 21.8 mmol CO 2 /m 2 /s (fixed). Among pepper varieties within a species, P n also varied more in our experiment than it did in others (Ghasemi et al, 2016;Rosado-Souza et al, 2015). Borisev et al 2012reported that the P n of 10 C. annuum varieties differed from 14.5 to 16.6 mmol CO 2 /m 2 /s (fixed); the C. annuum variety P n (22 varieties) in our work ranged from 3.7 to 16.3 mmol CO 2 /m 2 /s (fixed) ( Table 1).…”
Section: Discussionmentioning
confidence: 40%
“…Capsicum P n values varied more in our experiment (3.6-3.7 to 16.3 mmol CO 2 /m 2 /s fixed) than they did in other experiments reported by others; for example, Ou and Zou (2012) reported that the P n of five Capsicum species varied from 15.8 to 21.8 mmol CO 2 /m 2 /s (fixed). Among pepper varieties within a species, P n also varied more in our experiment than it did in others (Ghasemi et al, 2016;Rosado-Souza et al, 2015). Borisev et al 2012reported that the P n of 10 C. annuum varieties differed from 14.5 to 16.6 mmol CO 2 /m 2 /s (fixed); the C. annuum variety P n (22 varieties) in our work ranged from 3.7 to 16.3 mmol CO 2 /m 2 /s (fixed) ( Table 1).…”
Section: Discussionmentioning
confidence: 40%
“…The stress produced by SA modifies the quality and quantity of the essential oil of yarrow (Achillea millefolium) [ 18 ]. The content and compounds of essential oil are different in the chamomile flower and they depend on genotype, and environmental factors such as light intensity, day length, temperature, habitat, management of production and post-harvest processes [ 19 , 20 ]. Jeshni et al indicated that drought stress caused significant effects on physiological traits, essential oil yield, and essential oil components.…”
Section: Introductionmentioning
confidence: 99%
“…The greenhouse effect increases the temperature in the world and changes the climates, therefore heat is becoming a major abiotic stress and has been recognized as an agrarian effect in various semi-arid and arid regions. High temperature creates a series of physiological and biochemical modifications in plants, which affect plant growth and development and can lead to acute reduction in economic yields [ 12 , 13 ]. Unfortunately, there is not enough information about the possible effect of heat stress on metabolite production and biological activities of medicinal plants.…”
Section: Introductionmentioning
confidence: 99%